Pedagogical innovations and structural barriers in cultivating participatory civic skills in Indonesian higher education - Lisa Retnasari; Aim Abdulkarim; Dadang Sundawa; Prayoga Bestari; Ella Kusuma Wardani; Sulaiman (Universitas Negeri Yogyakarta, 2026)
This study addresses a critical gap in the literature on cultivating participatory civic skills in higher education in the digital era. While the importance of such skills is widely acknowledged, little is known about how educators practically conceptualise and assess them. Employing a qualitative phenomenological approach, this research collected data through open-ended questionnaires completed by Civic Education lecturers from diverse higher education institutions across Indonesia. The data were analysed using reflective thematic analysis. The findings show that lecturers demonstrate a robust theoretical understanding of participatory civic skills; this conceptual grasp does not systematically translate into assessment practices that effectively measure participatory learning outcomes. Although pedagogical innovations such as project-based learning and digital platform integration are being adopted to create more authentic learning experiences, their implementation is hindered by structural barriers. These include excessive administrative workloads, inflexible curricula, and inadequate technological infrastructure. Theoretically, this study contributes by highlighting the critical disconnect between pedagogical theory and assessment praxis in civic education. In practice, it underscores that fostering participatory skills necessitates not only classroom-level innovation but also institutional reforms, specifically rationalising workloads, increasing curricular flexibility, and developing authentic assessment models tailored for digital-era civic learning.